2017
DOI: 10.1038/srep46627
|View full text |Cite
|
Sign up to set email alerts
|

Sensory system plasticity in a visually specialized, nocturnal spider

Abstract: The interplay between an animal’s environmental niche and its behavior can influence the evolutionary form and function of its sensory systems. While intraspecific variation in sensory systems has been documented across distant taxa, fewer studies have investigated how changes in behavior might relate to plasticity in sensory systems across developmental time. To investigate the relationships among behavior, peripheral sensory structures, and central processing regions in the brain, we take advantage of a dram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 63 publications
(97 reference statements)
1
25
0
1
Order By: Relevance
“…Many studies have shown experience‐dependent plasticity of the MB calyces in Hymenoptera (Withers et al , ; ; ; Gronenberg et al , ; Fahrbach et al , ; Farris et al , ; Kühn‐Bühlmann and Wehner, ; Molina and O'Donnell, ; Maleszka et al , ; Stieb et al , ; Jones et al , ; Amador‐Vargas et al , ; Rehan et al , ), other insects (Montgomery et al , ; van Dijk et al , ; Montgomery and Merrill, ) and even a spider (Stafstrom et al , ). Fahrbach et al () showed that honeybee foragers that spend the winter in the hive without foraging had similar MB development to other foragers of younger age but similar experience.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown experience‐dependent plasticity of the MB calyces in Hymenoptera (Withers et al , ; ; ; Gronenberg et al , ; Fahrbach et al , ; Farris et al , ; Kühn‐Bühlmann and Wehner, ; Molina and O'Donnell, ; Maleszka et al , ; Stieb et al , ; Jones et al , ; Amador‐Vargas et al , ; Rehan et al , ), other insects (Montgomery et al , ; van Dijk et al , ; Montgomery and Merrill, ) and even a spider (Stafstrom et al , ). Fahrbach et al () showed that honeybee foragers that spend the winter in the hive without foraging had similar MB development to other foragers of younger age but similar experience.…”
Section: Discussionmentioning
confidence: 99%
“…Our contrasting results with our previous study on M. genalis may also result from the limited sample sizes in each study (Smith et al 2010). Many studies have shown experience-dependent plasticity of the MB calyces in Hymenoptera (Withers et al 1993, Gronenberg et al 1996, Fahrbach et al 1998, Farris et al 2001, Kuhn-Buhlman and Wehner 2006, Maleszka et al 2009, Molina and O'Donnell 2008, Stieb et al 2010, Jones et al 2013, Amador-Vargas et al 2015, Rehan et al 2015, other insects (Montgomery and Merrill 2016, Motgomery et al 2017, van Dijk et al 2017) and even a spider (Stafstrom et al 2017). Fahrbach et al (2003) showed that honeybee foragers that spend the winter in the hive without foraging had similar MB development to other foragers of younger age but similar experience.…”
Section: Author Manuscriptmentioning
confidence: 57%
“…Thus, scientists who study soft tissue have increasingly been looking to micro-CT imaging. For example, developmental biologists have employed micro-CT imaging to track embryo development 17 , entomologists have employed it to study mating ethology in Drosophila 18 and brain morphology in honeybees 19 , and very recently arachnologists have employed the method towards advancing spider neuroanatomy 20 23 .…”
Section: Discussionmentioning
confidence: 99%